Traditional Crafts Of Uzbeks And Tajiks In Afghanistan: Carpet Weaving, Embroidery, And Textile Making Traditions (Eurasian Journal of History, Geography and Economics, 2026)
This article analyzes the traditional crafts of Uzbeks and Tajiks living in Afghanistan. It highlights the rich cultural heritage, techniques, and traditions in carpet weaving, embroidery, textile and yarn production, leatherwork, glasswork, ceramics, and jewelry. The article provides a detailed account of the crafting processes, materials used, patterns, colors, and their significance in local and international markets. Furthermore, it compares the crafts of three ethnic groups (Uzbek, Tajik, Turkmen), demonstrating their cultural and social importance